[18F]FDG PET/MRI in the follow-up of hepatocellular carcinoma after liver transplantation. Issue 3 (11th January 2022) - Zucchetta, Pietro; Lacognata, Carmelo; Girardi, Francesca; Spimpolo, Alessandro; Crimì, Filippo; Cabrelle, Giulio; Zanon, Chiara; Boccagni, Patrizia; Evangelista, Laura; Cecchin, Diego; Cillo, Umberto
Abstract : Background: There is limited evidence regarding the application of [ 18 F] fluorodeoxyglucose (FDG)-PET/MRI in patients with a suspected clinical recurrence, who underwent liver transplantation for hepatocellular carcinoma (HCC). Therefore, we compared the accuracy of PET/MR and standard-of-care (SOC) imaging in these patients. Methods: We retrospectively reviewed 26 patients, whose liver were transplanted for HCC and were suspected of disease relapse based on biochemical analysis or SOC follow-up imaging, and carried out PET/MRI with diffusion-weighted imaging sequences on them. All patients underwent SOC imaging within the 2 months prior to the PET/MRI examination and had follow-up data for at least 12 months after. Reference standards were histopathology, clinical and imaging follow-up data. Results: Sensitivity, specificity, positive predictive value, negative predictive value and accuracy for PET/MRI were 100, 94, 91, 100 and 96%, whereas for SOC imaging were 80, 69, 61, 85 and 73%. The accuracy of PET/MRI was higher with respect to SOC imaging, although not significantly. Conclusions: PET/MRI is useful for oncological surveillance of patients who have undergone liver transplantation for HCC, particularly in cases of allergy to contrast media, renal failure or persistently elevated alpha-fetoprotein levels, and with no identification of metastatic/relapsing foci at standard-of-care imaging.